1991
DOI: 10.1111/j.1432-1033.1991.tb15778.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure/function relationship of proteins belonging to the family of receptors coupled to GTP‐binding proteins

Abstract: The structural properties of a number of proteins belonging to the family of receptors coupled to GTP binding proteins are discussed in relation to their function.The structure of the ligand binding site and of the regions involved in coupling to the G proteins are analyzed mainly for the adrenergic and muscarinic cholinergic receptors, for which site-directed mutagenesis and chimaeric constructions have been studied. The structure of the genes are compared and the presence of various regulatory elements is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
3

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(81 citation statements)
references
References 65 publications
1
77
0
3
Order By: Relevance
“…2). Because our preparations are not contaminated with blood cell components including lymphocytes, as assessed by immunoblotting for specific blood cell markers 2 and based on the apparent monospecificity of the antibodies (no cross-reaction with Syk, ZAP 70, Src and Fyn), 3 it appears that the endothelium expressed several different NRTK on its cell surface including Lck. Also the distinct differences in band pattern and Triton solubility (see below) for each of the NRTK suggested that the antibodies recognized different proteins and were not cross-reactive within this group of NRTK.…”
Section: Resultsmentioning
confidence: 99%
“…2). Because our preparations are not contaminated with blood cell components including lymphocytes, as assessed by immunoblotting for specific blood cell markers 2 and based on the apparent monospecificity of the antibodies (no cross-reaction with Syk, ZAP 70, Src and Fyn), 3 it appears that the endothelium expressed several different NRTK on its cell surface including Lck. Also the distinct differences in band pattern and Triton solubility (see below) for each of the NRTK suggested that the antibodies recognized different proteins and were not cross-reactive within this group of NRTK.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that actions mediated by galanin receptors involve pertussis toxin-ADP-ribosylable G proteins of inhibitory (Gi) or regulatory (Go) type (20)(21)(22). Furthermore, crosslinking studies using 125I-labeled galanin have shown that the molecular size of the receptor in SDS gels was 54 kDa (23), close to the value found for most G protein-coupled receptors with seven membrane-spanning domains (24). The cDNA coding for the galanin receptor or its subtypes has not yet been cloned; thus subtyping of galanin receptors must be based on comparing rank order of potency of different galanin-receptor agonists and antagonists.…”
mentioning
confidence: 85%
“…This G protein complex in turn activates a variety of second messenger systems, including a decrease in cyclic AMP and an increase in intracellular calcium (10). However, there are reports of NPY receptors coupled to phosphoinositol metabolism, suggesting the existence ofadditional receptor subtypes and/or multiple functions for the Y1 and Y2 subtypes (6,11).…”
mentioning
confidence: 97%
“…The corrected rat receptor sequence shows 94% identity to the human HY1 sequence. Analysis of the amino acid sequence of HY1 shows features typical of G protein-coupled receptors (10). These include seven hydrophobic putative membrane-spanning regions as well as potential glycosylation sites (Fig.…”
mentioning
confidence: 99%